A comparison of air-cell and gel surgical table pads and an evaluation of the influence of pressure distribution and other factors on pressure injury prevention. Issue 1 (February 2021) - Guzman, Sandra; Allegretti, Ana L.; Kormos, Robert L.; Brienza, David M.
Abstract: Guidelines for pressure injury prevention consider the use of pressure-redistributing pads to prevent tissue deformation. However, limited research exists to assess the pressure distribution provided by the operating tables and the effectiveness of pressure-redistributing pads in preventing pressure injuries. In this study, we compared the pressure distribution properties of two surgical table pads and identified parameters influencing pressure injury outcomes after a lengthy surgical procedure. Twenty-seven patients undergoing left ventricular assist device implantation surgery participated in the study. Participants were randomly assigned to use either an air cell-based pad or a gel pad. Interface pressure was recorded during the surgery. We analyzed the effect of surgical table pad type, interface pressure distribution and pressure injury outcomes and analyzed what characteristics of the patients and the interface pressure are most influential for the development of pressure injuries. Comparing the interface pressure parameters between the air-cell group and the gel group, only the peak pressure index x time was significantly different (p < 0.05). We used univariate logistic regression analysis to identify significant predictors for the pressure injury outcome. The support surface was not significant. And, among patient characteristics, only age and BMI were significant (p ≤ 0.05). Among the interface pressure parameters, pressure density maxima, peak pressure index x time, and coefficient of variation were significant for pressure injury outcome (p ≤ 0.05). Peak pressure index, average pressure, and the surgery length were not statistically significant for pressure injury outcomes. Graphical abstract: Image 1 Highlights: Air cell surgical pads resulted in fewer pressure injuries compared to the gel pads. The surgical pad was not a significant indicator of the pressure injury outcome. Pressure distribution associated with pads was a significant factor for pressure injury. Pressure density maxima is a candidate pressure metric for real-time pressure injury risk. A statistical model with age, BMI, pressure density maxima predicted pressure injury.